Preparation method of copper or copper alloy foil EBSD sample
Through adhesive and thermal inlay technology, the copper or copper alloy foil is closely combined, and combined with grinding and polishing and vibration polishing, the problems of surface treatment difficulty and complex process parameters in the preparation of copper foil sample are solved, achieving high efficiency, Stable flat and good conductivity EBSD sample preparation.
Patent Information
- Application Number
- CN202411486045.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2024-12-20
AI Technical Summary
In the prior art, copper or copper alloy foils are thin and easy to bend when preparing EBSD samples, and the surface treatment is difficult, the electrolytic polishing process parameters are complex and unstable. Conventional inlay methods lead to uneven surface surfaces and electrolytes. High risk.
Adhesives to adhere copper or copper alloy foil to the surface of the metal block and heat-insert them to make them tightly bonded. Then, by grinding and vibration polishing, a flat and wrinkle-free sample is obtained, avoiding electrolytic polishing. Exploration of process and use of electrolytes.
The surface of the EBSD sample of copper or copper alloy foil is flat and has good conductivity, time-saving and efficient, and the calibration rate of the Kikuchi flower pattern is high, which solves the problems of difficulty in sample preparation and complex process parameters, and is safe and reliable.
Smart Images

Figure CN119164734A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sample preparation, and in particular relates to a method for preparing an EBSD sample of copper or copper alloy foil. Background Art
[0002] According to GB / T 5187-2008 "Copper and Copper Alloy Foil", copper materials with a thickness of less than 0.15mm are called copper foil. Copper foil is an important basic material in the fields of electronics and electrodes. According to the thickness, copper foil can be divided into ultra-thick copper foil (>100μm), thick copper foil (70μm-100μm), conventional copper foil (20μm-70μm), and thin copper foil (<20μm). Thin copper foil with a thickness of 6μm-20μm is mainly used as a carrier of negative electrode materials in lithium-ion batteries; conventional copper foil with a thickness of 12μm-70μm is mainly used in electronic information fields such as printed circuit boards; and ultra-thick copper foil with a thickness of >100μm can be used as electromagnetic signal shielding materials in the aerospace field. With the advancement of science and technology, the performance requirements of copper and copper foil in various fields are also constantly improving. Excellent performance is closely related to the microstructure, so it is very important to study the microstructure of copper and copper foil materials. EBSD technology can combine microstructure and crystallographic analysis, and has become a convenient and efficient analytical method in modern materials research.
[0003] Since the foil is thin and the surface is easy to bend and deform, it is difficult to prepare the sample surface before electrolytic polishing. To obtain a good electrolytic effect, it is necessary to try different electrolyte ratios and electrolytic parameters. It takes a long time to explore the optimal process parameters, and the electrolytic surface quality is unstable. In addition, the electrolyte is mostly strong acid, which is highly dangerous. If the foil is prepared by conventional mounting methods, it is not easy for the foil to be tightly combined with the solidified mounting block, and wrinkles and bubbles will occur on the surface. The uneven foil cannot be prepared into a smooth and bright sample through grinding and polishing. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a method for preparing an EBSD sample of copper or copper alloy foil in view of the deficiencies of the above-mentioned prior art. The method uses an adhesive to adhere the copper or copper alloy foil to the surface of a metal block, and performs hot mounting, so that the copper or copper alloy foil is tightly combined with the metal block, and then through subsequent grinding and vibration polishing, a copper or copper alloy foil EBSD sample with a smooth surface, no wrinkles, no bubbling, and good conductivity can be obtained. There is no need to explore the electrolytic polishing process parameters, which is time-saving and efficient, and the Kikuchi pattern calibration rate of the sample is high, which solves the problems of difficult sample preparation, complex process parameters, and uneven sample surface in the conventional mounting method in the preparation method of the metal foil electrolytic polishing.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing an EBSD sample of copper or copper alloy foil, characterized in that the method comprises the following steps:
[0006] Step 1: Use aviation scissors to cut copper or copper alloy foil, and then use adhesive to adhere the copper or copper alloy foil to the bottom of a metal block with a smooth surface, and add a counterweight to the metal block to ensure that the copper or copper alloy foil is tightly bonded to the surface of the metal block, and then fold the part that is not in contact with the metal block toward the surface of the metal block perpendicular to the bonding surface to obtain a processed foil;
[0007] Step 2: hot-mounting the treated foil obtained in step 1 to obtain a mounting block;
[0008] Step 3, mechanically grinding and automatically polishing the mounted sample block obtained in step 2;
[0009] Step 4: Vibration polishing is performed on the mounted sample block after the automatic mechanical polishing treatment in step 3, and after cleaning, a copper or copper alloy foil EBSD sample is obtained.
[0010] The above-mentioned method for preparing an EBSD sample of a copper or copper alloy foil is characterized in that the diagonal length of the adhesion surface between the copper or copper alloy foil and the metal block in step 1 is less than the diameter of the mold cavity of the mounting machine used for the hot mounting treatment in step 2. By limiting the diagonal length of the adhesion surface between the copper or copper alloy foil and the metal block to be less than the diameter of the mold cavity of the mounting machine, it is ensured that the processed foil can be loaded into the mold cavity of the mounting machine for smooth mounting.
[0011] The above-mentioned method for preparing a copper or copper alloy foil EBSD sample is characterized in that the surface area of the copper or copper alloy foil in step 1 is larger than the bonding surface area of the corresponding adhered metal block. Through this limitation, it is ensured that the part of the copper or copper alloy foil that is not in contact with the metal block is folded toward the surface of the metal block perpendicular to the bonding surface, and the folded part is embedded in the mounting block during the subsequent hot mounting process and firmly combined, so that the copper or copper alloy foil on the bonding surface is prevented from falling off, wrinkling, and bubbling when it is polished, thereby improving the quality of the copper or copper alloy foil EBSD sample.
[0012] The above-mentioned method for preparing an EBSD sample of a copper or copper alloy foil is characterized in that the heat-resistant temperature of the adhesive in step 1 is higher than 150° C. By using an adhesive with a heat-resistant temperature higher than 150° C., it is prevented from failing at a hot mounting temperature of 120° C. to 150° C., and the copper or copper alloy foil is prevented from separating from the surface of the metal block and bubbling.
[0013] The above-mentioned method for preparing a copper or copper alloy foil EBSD sample is characterized in that the mounting powder used in the hot mounting treatment in step 2 is a conductive hot mounting powder. Commonly used mounting powders are non-conductive general hot mounting resins. After the sample preparation is completed, the sample needs to be taken out from the mounting block for testing, which causes the thinner copper or copper alloy foil to be easily bent or damage the test surface when it is taken out. Therefore, the present invention uses a conductive hot mounting powder, which can be directly tested after the sample preparation is completed, without taking the copper or copper alloy foil out of the mounting block, thereby ensuring the quality of the copper or copper alloy foil EBSD sample.
[0014] The above-mentioned method for preparing a copper or copper alloy foil EBSD sample is characterized in that the mechanical polishing in step 3 is performed by using 1000# to 2000# water sandpaper. The above-mentioned fine sandpaper is used to mechanically polish the mounting block to avoid grinding through the thin copper or copper alloy foil caused by polishing with coarse sandpaper with a larger mesh number, thereby ensuring the quality of the copper or copper alloy foil EBSD sample.
[0015] The above-mentioned method for preparing an EBSD sample of copper or copper alloy foil is characterized in that the automatic polishing liquid used in the automatic mechanical polishing treatment in step three is a mixed suspension of silicon dioxide and hydrogen peroxide with a particle size of 0.05 μm.
[0016] The above-mentioned method for preparing an EBSD sample of a copper or copper alloy foil is characterized in that the parameters of the automatic polishing machine used in the automatic mechanical polishing treatment in step three are: chuck rotation speed 100r / min~150r / min, flannel polishing disc rotation speed 100r / min~150r / min, polishing time 5min~10min.
[0017] The above-mentioned method for preparing an EBSD sample of copper or copper alloy foil is characterized in that the vibration polishing liquid used in the vibration polishing treatment in step 4 is a silicon dioxide polishing liquid with a particle size of 0.02 μm.
[0018] The above-mentioned method for preparing an EBSD sample of copper or copper alloy foil is characterized in that the process parameters of the vibration polishing treatment in step 4 are: sample fixture weight 10N, amplitude 40% to 60%, vibration time 4h to 6h, and ethanol cleaning and drying after completion. By controlling the fixture weight, amplitude and automatic time, the vibration polishing effect of the thinner copper or copper alloy foil in the mounted sample block after mechanical polishing is guaranteed, and a sample with a smooth and bright surface is obtained.
[0019] Compared with the prior art, the present invention has the following advantages:
[0020] 1. Compared with the traditional mounting method, the present invention uses an adhesive to adhere the copper or copper alloy foil to the surface of the metal block, and then performs hot mounting, so that the copper or copper alloy foil is tightly combined with the metal block, and a smooth and bright sample is obtained through subsequent grinding and polishing. The surface of the copper or copper alloy foil EBSD sample obtained is smooth, without wrinkles or bubbling, and has good conductivity.
[0021] 2. Compared with the electrolytic polishing method, the present invention obtains a mounting block with a smooth surface by using an adhesive and hot mounting, so that the copper or copper alloy foil EBSD sample can be obtained through subsequent grinding, polishing and vibration polishing. There is no need to use electrolytic polishing and explore electrolytic process parameters. It is time-saving and efficient, with stable effects and safety and reliability. The Kikuchi pattern calibration rate of the copper or copper alloy foil EBSD sample is high, reaching more than 97%.
[0022] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a schematic diagram of the structure in which the copper or copper alloy foil of the present invention is adhered to a metal block and folded.
[0024] Figure 2 It is a schematic diagram of the mounting block of the present invention.
[0025] Figure 3 This is the grain orientation distribution diagram of the EBSD sample of the copper alloy foil with a thickness of 100 μm prepared in Example 1 of the present invention.
[0026] Figure 4 This is the grain orientation distribution diagram of the EBSD sample of the copper foil with a thickness of 48 μm prepared in Example 2 of the present invention.
[0027] Figure 5 This is the grain orientation distribution diagram of the EBSD sample of the copper foil material with a thickness of 12 μm prepared in Example 3 of the present invention. DETAILED DESCRIPTION
[0028] Example 1
[0029] This embodiment includes the following steps:
[0030] Step 1: Use aviation scissors to cut a copper alloy foil with a length × width × thickness of 20 mm × 20 mm × 0.1 mm, and then use an epoxy adhesive with a heat-resistant temperature of 200°C to adhere the copper alloy foil to the bottom of a metal block with a length × width × thickness of 15 mm × 15 mm × 15 mm and a smooth surface, and add a counterweight to the metal block to ensure that the copper alloy foil is tightly combined with the surface of the metal block, and then fold the part that is not in contact with the metal block in a direction perpendicular to the surface of the metal block to obtain a treated foil, such as Figure 1 As shown;
[0031] Step 2: Place the processed foil obtained in step 1 into the cavity of the mounting machine, and use conductive hot mounting powder to perform hot mounting treatment on the processed foil to obtain a cylindrical mounting block with a diameter of Φ30 mm, such as Figure 2 As shown;
[0032] Step 3: Use 1000# water sandpaper to mechanically polish the test surface of the mounted block obtained in step 2, and then use an automatic polishing liquid of a mixed suspension of silicon dioxide and hydrogen peroxide with a particle size of 0.05μm to perform automatic mechanical polishing on the polished surface until there is no obvious sandpaper mark on the surface; the automatic polishing machine fixture used for the automatic mechanical polishing process has a diameter of Φ30mm, and the working parameters are: chuck rotation speed 150r / min, flannel polishing disc rotation speed 150r / min, polishing time 10min;
[0033] Step 4: Use a silica polishing liquid with a particle size of 0.02 μm to perform vibration polishing on the mounted sample block after automatic mechanical polishing in step 3 to remove surface stress. During vibration polishing, the sample fixture diameter is Φ30 mm, the counterweight is 10 N, the amplitude is 60%, and the vibration time is 6 h. After the end, it is cleaned and dried with ethanol to obtain a copper alloy foil EBSD sample with a thickness of 100 μm.
[0034] Figure 3 The grain orientation distribution diagram of the EBSD sample of the copper alloy foil with a thickness of 100 μm prepared in this embodiment is shown in FIG. Figure 3 The calculated original calibration rate of the copper alloy foil EBSD sample is 98.6%.
[0035] Example 2
[0036] This embodiment includes the following steps:
[0037] Step 1: Use aviation scissors to cut a copper foil material with a length × width × thickness of 20 mm × 20 mm × 0.048 mm, and then use an epoxy adhesive with a heat-resistant temperature of 200°C to adhere the copper foil material to the bottom of a metal block with a length × width × thickness of 15 mm × 15 mm × 5 mm and a smooth surface, and add a counterweight to the metal block to ensure that the copper alloy foil material is tightly bonded to the surface of the metal block, and then fold the part that is not in contact with the metal block in a direction perpendicular to the surface of the metal block to obtain a treated foil material, such as Figure 1 As shown;
[0038] Step 2: Place the processed foil obtained in step 1 into the cavity of the mounting machine, and use conductive hot mounting powder to perform hot mounting treatment on the processed foil to obtain a cylindrical mounting block with a diameter of Φ30 mm, such as Figure 2 As shown;
[0039] Step 3: Use 1500# water sandpaper to mechanically polish the test surface of the mounted block obtained in step 2, and then use an automatic polishing liquid of a mixed suspension of silicon dioxide and hydrogen peroxide with a particle size of 0.05μm to perform automatic mechanical polishing on the polished surface until there is no obvious sandpaper mark on the surface; the automatic polishing machine fixture used for the automatic mechanical polishing process has a diameter of Φ30mm, and the working parameters are: chuck rotation speed 120r / min, flannel polishing disc rotation speed 120r / min, polishing time 8min;
[0040] Step 4: Use a silica polishing liquid with a particle size of 0.02 μm to perform vibration polishing on the mounted sample block after automatic mechanical polishing in step 3 to remove surface stress. During vibration polishing, the sample fixture diameter is Φ30 mm, the counterweight is 10 N, the amplitude is 50%, and the vibration time is 5 h. After the end, it is cleaned and dried with ethanol to obtain a copper foil EBSD sample with a thickness of 48 μm.
[0041] Figure 4 This is the grain orientation distribution diagram of the EBSD sample of the copper foil with a thickness of 48 μm prepared in this embodiment. Figure 4 The calculated original calibration rate of the copper foil EBSD sample is 97.4%.
[0042] Example 3
[0043] This embodiment includes the following steps:
[0044] Step 1: Use aviation scissors to cut a copper alloy foil with a length × width × thickness of 20 mm × 20 mm × 0.012 mm, and then use an epoxy adhesive with a heat-resistant temperature of 200°C to adhere the copper alloy foil to the bottom of a metal block with a length × width × thickness of 15 mm × 15 mm × 5 mm and a smooth surface, and add a counterweight to the metal block to ensure that the copper alloy foil is tightly bonded to the surface of the metal block, and then fold the part that is not in contact with the metal block in a direction perpendicular to the surface of the metal block to obtain a treated foil, such as Figure 1 As shown;
[0045] Step 2: Place the processed foil obtained in step 1 into the cavity of the mounting machine, and use conductive hot mounting powder to perform hot mounting treatment on the processed foil to obtain a cylindrical mounting block with a diameter of Φ30 mm, such as Figure 2 As shown;
[0046] Step 3: Use 2000# water sandpaper to mechanically polish the test surface of the mounted block obtained in step 2, and then use an automatic polishing liquid of a mixed suspension of silicon dioxide and hydrogen peroxide with a particle size of 0.05 μm to perform automatic mechanical polishing on the polished surface until there is no obvious sandpaper mark on the surface; the automatic polishing machine fixture used for the automatic mechanical polishing process has a diameter of Φ30 mm, and the working parameters are: chuck rotation speed 100 r / min, flannel polishing disc rotation speed 100 r / min, polishing time 5 min;
[0047] Step 4: Use a silica polishing liquid with a particle size of 0.02 μm to perform vibration polishing on the mounted sample block after automatic mechanical polishing in step 3 to remove surface stress. During vibration polishing, the sample fixture diameter is Φ30 mm, the counterweight is 10 N, the amplitude is 40%, and the vibration time is 4 h. After the end, it is cleaned and dried with ethanol to obtain a copper foil EBSD sample with a thickness of 12 μm.
[0048] Figure 5 This is the grain orientation distribution diagram of the EBSD sample of the copper foil with a thickness of 12 μm prepared in this embodiment. Figure 5 The calculated original calibration rate of the copper foil EBSD sample is 98.4%.
[0049] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing an EBSD sample of copper or copper alloy foil, characterized in that: The method comprises the following steps: Step 1: Use aviation scissors to cut copper or copper alloy foil, and then use adhesive to adhere the copper or copper alloy foil to the bottom of a metal block with a smooth surface, and add a counterweight to the metal block to ensure that the copper or copper alloy foil is tightly bonded to the surface of the metal block, and then fold the part that is not in contact with the metal block toward the surface of the metal block perpendicular to the bonding surface to obtain a processed foil; Step 2: hot-mounting the treated foil obtained in step 1 to obtain a mounting block; Step 3, mechanically grinding and automatically polishing the mounted sample block obtained in step 2; Step 4: Vibration polishing is performed on the mounted sample block after the automatic mechanical polishing treatment in step 3, and after cleaning, a copper or copper alloy foil EBSD sample is obtained.
2. The method for preparing a copper or copper alloy foil EBSD sample according to claim 1, characterized in that: The diagonal length of the adhesion surface between the copper or copper alloy foil and the metal block in step one is smaller than the cavity diameter of the mounting machine used in the hot mounting treatment in step two.
3. The method for preparing a copper or copper alloy foil EBSD sample according to claim 1, characterized in that: The surface area of the copper or copper alloy foil in step 1 is larger than the bonding surface area of the corresponding adhesive metal block.
4. The method for preparing a copper or copper alloy foil EBSD sample according to claim 1, characterized in that: The heat-resistant temperature of the adhesive in step 1 is higher than 150°C.
5. The method for preparing a copper or copper alloy foil EBSD sample according to claim 1, characterized in that: The inlay powder used in the hot inlay treatment in step 2 is conductive hot inlay powder.
6. The method for preparing a copper or copper alloy foil EBSD sample according to claim 1, characterized in that: The mechanical grinding described in step 3 is grinding using 1000# to 2000# water sandpaper.
7. The method for preparing a copper or copper alloy foil EBSD sample according to claim 1, characterized in that: The automatic polishing liquid used in the automatic mechanical polishing treatment in step 3 is a mixed suspension of silicon dioxide and hydrogen peroxide with a particle size of 0.05 μm.
8. The method for preparing a copper or copper alloy foil EBSD sample according to claim 1, characterized in that: The parameters of the automatic polishing machine used in the automatic mechanical polishing process in step 3 are: chuck rotation speed 100r / min~150r / min, flannel polishing disc rotation speed 100r / min~150r / min, polishing time 5min~10min.
9. The method for preparing a copper or copper alloy foil EBSD sample according to claim 1, characterized in that: The vibration polishing liquid used in the vibration polishing treatment in step 4 is a silicon dioxide polishing liquid with a particle size of 0.02 μm.
10. The method for preparing a copper or copper alloy foil EBSD sample according to claim 1, characterized in that: The process parameters of the vibration polishing treatment in step 4 are: sample fixture weight 10N, amplitude 40% to 60%, vibration time 4h to 6h, and ethanol cleaning and drying after completion.
Citation Information
Patent Citations
Preparation method of ultrathin metal material metallographic sample
CN117030410A
Sample fixing assembly for statistical analysis of inclusions of cold-rolled sheet and preparation method of sample fixing assembly
CN117451458A
Sample preparation method of titanium alloy foil EBSD sample
CN117451758A
Method for producing metal foil-clad laminated sheet
JP2000229374A
